THE EFFECTIVENESS OF INDIGENOUS ENDOMYCORRHIZA AND RHIZOBIUM INOCULUM IN INCREASING NUTRIENT UPTAKE AND YIELD OF SOYBEAN IN DRY LAND - Kiuk, Yosni; Rai, I Nyoman; Kesumadewi, Anak Agung Istri (International Journal of Biosciences and Biotechnology, 2020)
Increasing the productivity of soybeans in dry land can be done by designing a package of fertilizer technology based on biological materials using indigenous endomycorrhiza and Rhizobium. The application of indigenous endomycorrhizal biofertilizer combined with Rhizobium is expected to be able to improve nitrogen and phosporus uptake so as to increase the productivity of soybeans in dry land. The experiment used two-factor factorial randomized block design. The first factor was dose of endomycorrhizal spores of Glomus that consisted of four levels, namely, treatment without endomycorrhiza inoculation, dose of 50 endomycorrhizal spores, dose of 100 endomycorrhizal spores, and dose of 150 endomycorrhizal spores. The second factor was inoculation of Rhizobium inoculum that consisted of two levels, namely, treatment without Rhizobium inoculation and Rhizobium inoculation. The results showed that combination of 50 endomycorrhizal spores with Rhizobium inoculation gave the best effect on the number of effective root nodules per plant, endomycorrhizal infection per plant, nutrient uptake by plant, number of pods per plant, number of seeds per plant, and oven-dry weight of seeds per plant.